Imaging Early Oceanic Crust spreading in the Equatorial Atlantic Ocean: Insights from the MAGIC wide-angle experiment. (November 2021) - Moulin, Maryline; Schnurle, Philippe; Afilhado, Alexandra; Gallais, Flora; Dias, Nuno; Evain, Mikael; Soares, José; Fuck, Reinhardt; da Cruz Pessoa Neto, Otaviano; Viana, Adriano; Aslanian, Daniel; ,
Abstract: During the MAGIC (Margins of brAzil, Ghana, and Ivory Coast) experiment, five combined wide-angle, and reflection seismic profiles were acquired in the Pará-Maranhão/Barreirinhas/Ceará basins northern Brazil. This is a pull-apart passive margin, with two strike-slip borders. The equipment deployed includes 143 sea-bottom seismometers (OBS), a 4.5-km seismic streamer, and a 7587-in 3 airgun array. In this paper, we focus on the distal parts of three profiles, and one entire transverse NW-SE profile, located on the presumed Cretaceous oceanic crust. Forward modelling of these wide-angle data sets reveals an E-W lateral evolution of the oceanic crust spreading initiation with: 1) just after the so-called intermediate domain, 60 km-wide domain that consists of a 5-km-thick crystalline crust. The basement presents two layers characterized by high acoustic velocity. This domain is bounded to the NW by a NW-SE volcanic line (Volcano Alignment), and 2) a 5-km-thick oceanic crust consisting of two layers characterized by "normal velocities" spanning between the two main fracture zones that fringe the Pará-Maranhão-Barreirinhas-Ceará segment. Despite a similar thickness, these two sub-domains present different velocity distribution in their two layers. They are both overlain by 5.5 km of sedimentary deposits. Forward wide-angle modelling confirms that the seafloor spreading process was progressive, with firstly the emplacement of a proto-oceanic crust, and then a thin oceanic crust. The "proto-oceanic" crust presents a similar seismic velocity with the intermediate domain interpreted as exhumed lower continental crust except for the lower part where the intruded lower crust gives place to a very sharp Moho at the base of the proto-oceanic domain. By contrast, the thin oceanic crust domain has a lower velocity structure in its upper layer, that is interpreted as basalt and is absent in the proto-oceanic crust. This eastward evolution, as also observed in the Provençal Basin, and the Santos Basin, suggests the involvement of the lower continental crust in the first steps of seafloor spreading. Highlights: The Pará-Maranhão-Barreirinhas-Ceará passive margin in the Equatorial Atlantic segment presents a strong E-W-segmentation with: The transition to oceanic crust takes place in stages, with the presence of proto-oceanic crust before a "more typical" but still thin oceanic crust eastward This eastward evolution implies lower continental material flow inside a first proto-oceanic crust and some continental mantle lithosphere erosion.